2012
DOI: 10.1007/s00251-012-0606-4
|View full text |Cite
|
Sign up to set email alerts
|

Breadth of the CD4+ T cell response to Anaplasma marginale VirB9-1, VirB9-2 and VirB10 and MHC class II DR and DQ restriction elements

Abstract: MHC class II molecules influence antigen-specific CD4+ T-lymphocyte responses primed by immunization and infection. CD4+ T-cell responses are important for controlling infection by many bacterial pathogens including Anaplasma marginale, and are observed in cattle immunized with the protective A. marginale outer membrane (OM) vaccine. Immunogenic proteins that comprise the protective OM vaccine include type IV secretion system (T4SS) proteins VirB9-1, VirB9-2, and VirB10, candidates for inclusion in a multi-epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 45 publications
(74 reference statements)
3
21
0
1
Order By: Relevance
“…This afforded an unique opportunity to examine the functionality of MoMΦ in a genetically defined context with a source of autologous cells where experiments could be duplicated as needed (Morse et al . ). A control peptide, peptide 8 of the VirB9‐1 protein had been identified which is not recognized by the MHC II allomorph expressed by the DRB3 haplotype *1101.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This afforded an unique opportunity to examine the functionality of MoMΦ in a genetically defined context with a source of autologous cells where experiments could be duplicated as needed (Morse et al . ). A control peptide, peptide 8 of the VirB9‐1 protein had been identified which is not recognized by the MHC II allomorph expressed by the DRB3 haplotype *1101.…”
Section: Discussionmentioning
confidence: 97%
“…As a proof of concept, to show that the PLGA/MPLA NPs loaded with antigen could stimulate CD4 T cells, we used T cells from a calf that had been previously immunized with A. marginale OM expressing MHC II DRB3 haplotype *1101, which was shown to respond to peptide 5 of VirB9-2, but not peptide 8 of VirB9-1 (Morse et al 2012). PLGA/MPLA NP were loaded with each peptide (as described above) and tested with free peptide in a proliferation assay using a short-term T-cell line, started from PBMC stimulated with OM for 1 week and rested with APC without antigen for 1 week.…”
Section: T-cell Stimulation Assaymentioning
confidence: 99%
“…Therefore, it is desirable to express soluble VirB9-1 and VirB10 proteins. VirB9-1 and VirB10 have been previously expressed in bacteria using FLAG-tag or His-tag technologies, however both yielded insoluble proteins likely due to their intrinsic properties as outer membrane proteins [11,13]. This issue has been addressed in the current study, by producing soluble VirB9-1 and VirB10 using the yeast P. pastoris expression system.…”
Section: Discussionmentioning
confidence: 98%
“…To date expression of VirB9-1 and VirB10 has been reported using the FLAG-tag (a polypeptide protein tag) or His-tag systems, resulting in insoluble products presumably due to their intrinsic properties as membrane proteins [11,13]. Recently, the methylotrophic Pichia pastoris has rapidly become a highly successful system for the expression of heterologous proteins and is considered faster, easier, and less expensive than insect or mammalian protein expression systems [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Lotteau et al (32,33) identified the existence of mixed isotype DR␣-DQ␤ hybrid dimers in B-cell lines but could not identify any DQ␣-DR␤ mixed isotype dimers. Recently, mixed DQ␣-DR␤ isotype hybrid molecules (BoLA-DQA/DRB3) that were functional in presenting viral peptide to CD4 ϩ T-cells have been reported in cattle immunized with Anaplasma marginale vaccine (52).…”
Section: Discussionmentioning
confidence: 99%